2022
DOI: 10.1097/sap.0000000000003159
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Academic Cosmetic Surgery Practice

Abstract: Purpose Although growth in cosmetic surgery remains constant in the private setting, academic cosmetic surgery practices are often underdeveloped. Our study aims to determine which patient populations access academic cosmetic surgery services. Methods The 2018 Health Care Utilization Project Nationwide Ambulatory Surgery Sample database was used for data analysis. Encounters for the following American Society of Plastic Surgery top 5 procedures for 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…The analysis of our data reflects the prevalence of cosmetic surgery in Japan and its status of procedures. Compared with other countries, 10 the proportion of surgical procedures for the face, including the eyes and nose, were apparently higher in our group. Moreover, the Japan Society of Aesthetic Plastic Surgery, a Japanese academic society, has reported that 87.7% of cosmetic surgery was related to the face in the Japanese multicenter study that did not include our group data.…”
Section: Discussioncontrasting
confidence: 68%
“…The analysis of our data reflects the prevalence of cosmetic surgery in Japan and its status of procedures. Compared with other countries, 10 the proportion of surgical procedures for the face, including the eyes and nose, were apparently higher in our group. Moreover, the Japan Society of Aesthetic Plastic Surgery, a Japanese academic society, has reported that 87.7% of cosmetic surgery was related to the face in the Japanese multicenter study that did not include our group data.…”
Section: Discussioncontrasting
confidence: 68%
“…5 In their analysis of patient utilization patterns in academic cosmetic surgery practices using the 2018 Nationwide Ambulatory Surgery Sample database, Moore et al noted that breast augmentation rates were higher among low-income patients compared with their high-income counterparts. 10 Thus, it appears that income levels do not always correlate with cosmetic procedure utilization. However, we believe our interpretation of financial stability/prowess as inflexible/flexible consumer spending provides greater real-world value because it hones in on the aspect of personal finances that deals with actual spending on goods and services, which include cosmetic surgery utilization.…”
Section: Discussionmentioning
confidence: 99%